Impact of regional water supply, sanitation et hygiene (WASH) program in Senegal on rural livelihoods and sustainable development. (5th November 2021) - Sy, Ibrahima; Bodian, Ansoumana; Konté, Mamadou Abdoulaye; Diop, Lamine; Ndiaye, Papa Malick; Thiam, Sokhna; Mouanda, Joseph
Abstract: In 2006, Senegal benefited from the African Development Bank's (AfDB) Rural Water Supply and Sanitation Initiative (RWSSI) a WASH sub-program for 17, 100 households in rural areas in the regions of Louga, Ziguinchor and Kolda. A project results assessment was conducted in 2016 by the AfDB Independent Development Evaluation (IDEV) to measure the sub-program impacts on the living conditions of the communities. This approach allowed the measurement of project impacts based on comparative pre-and post-intervention data, as well as beneficiaries and non-beneficiaries' groups considering collected quantitative data (963 households, 38 schools, 23 health centres and 46 GPS points of infrastructures) and qualitative data (31 individual interviews and 4 focus group discussions). Several analyses (descriptive statistics, correlative analysis, effects and impact analysis with Average Treatment Effect (ATE) and cartographic treatment) were carried out to determine the project's results indicators as well as their overall effects. The results show an access rate of 73% for drinking water among beneficiaries against 6% among non-beneficiaries, and an access rate of 72% for sanitation (improved latrine) in the treatment areas against 33.7% in the control areas. In sub-program focus areas, an increase in the quantity of water used per household by 157 liters, a reduction in water price by 0.072 USD and reduction in time taken to supply drinking water of 65 minutes were observed. Also, it was noted a reduction in arduousness of carrying water by 2 km from the supply point, an increase in the schooling rate of children, especially girls, in income-generating activities, a decrease in the number of sick people avoided by 2 persons and increase in medical treatment avoided were noted. The progress made by the project's achievements demonstrate that improvement in water access, sanitation and hygiene access is one of the main drivers and levers of change and transformation of the households' living conditions in rural areas, often explaining the priority given to this area of intervention within the implementation of the MDGs and SDGs. HIGHLIGHTS Increase of water and sanitation level access in rural areas. Links between WASH and improved living conditions of communities. Water and sanitation are major issues for communities' sustainable development. Water and sanitation are main determinants for reducing poverty incidence, improving well-being and health and community development.